Community-Based Service-Learning: Does It Have a Role in Management Education? - Dumas, Colette (International journal of value-based management, 2002)
Community based service-learning is a form of experiential education in which students engage in activities that address human and community needs, together with structured opportunities designed to promote student learning and development. Can it be effectively applied to address the current struggles of management education? Management education is facing a gap between traditional curricular content and society's needs for new competencies. The Academy is also faced with the challenge of more effectively relating to society's social, economic and civic problems. The results of this analysis indicate that service-learning offers a means of closing the gap by helping to prepare students who are lifelong learners and active, caring participants in their communities. Service-learning appears to be a promising means of developing such managerial skills as leadership, critical thinking, teamwork, and cooperation. The limitations of service-learning for management education are addressed as well.